Preparation and Characterization of PEG4000 Palmitate/PEG8000 Palmitate-Solid Dispersion Containing the Poorly Water-Soluble Drug Andrographolide - Qingyun Zeng; Liquan Ou; Guowei Zhao; Ping Cai; Zhenggen Liao; Wei Dong; Xinli Liang (Advances in Polymer Technology)
Solid dispersion (SD) is the effective approach to improve the dissolution rate and bioavailability of class II drugs with low water solubility and high tissue permeability in the Biopharmaceutics Classification System. This study investigated the effects of polyethylene glycol (PEG) molecular weight in carrier material PEG palmitate on the properties of andrographolide (AG)-SD. We prepared SDs containing the poorly water-soluble drug AG by the freeze-drying method. The SDs were manufactured from two different polymers, PEG4000 palmitate and PEG8000 palmitate. The physicochemical properties of the AG-SDs were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, powder X-ray diffraction, scanning electron microscopy, dissolution testing, and so on. We found that AG-PEG4000 palmitate-SD and AG-PEG8000 palmitate-SD were similar in the surface morphology, specific surface area, and pore volume. Compared with the AG-PEG4000 palmitate-SD, the intermolecular interaction between PEG8000 palmitate and AG was stronger, and the thermal stability of AG-PEG8000 palmitate-SD was better. In the meanwhile, the AG relative crystallinity was lower and the AG dissolution rate was faster in AG-PEG8000 palmitate-SD. The results demonstrate that the increasing PEG molecular weight in the PEG palmitate can improve the compatibility between the poorly water-soluble drug and carrier material, which is beneficial to improve the SD thermal stability and increases the dissolution rate of poorly water-soluble drug in the SD.